A Preliminary Result on Electrical capacitance tomography for Gas-solid flow in pneumatic conveyor system. (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Electrical capacitance tomography (ECT) is categorized as a soft-field sensor which is non-invasive and non-intrusive instrument that can provide the visualization of cross-sectional distribution of any kind of multiphase flow. ECT would help in understanding the gas-solid flow interaction. This research is conducted to overcome some difficulties in measurement of gas-solid flows that exist in multiphase flows in pipelines or vessels such as the sedimentation of the solid and the velocity of the solid particles. Hence, the characterization of gas-solid two-phase flow by implementing an ECT system is necessary. Three objectives are set for this research which are the determination of an optimum frequency and amplitude for capacitance measurement of Poly-methyl methacrylate (PMMA) material by ECT system, the determination of the average solid velocity in gas-solid two-phase flow through cross-correlation method using Parseval’s theorem, and image reconstruction based on eight ECT sensors using Linear Back Projection (LBP) algorithm. This paper concise the theory of ECT system, existing works, proposed methodology, and the expected results.